FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN KONTRASEPSI IUD PADA WUS SAAT PANDEMI DI PUSKESMAS KECAMATAN CILINCING TAHUN 2021 - Thalia Altamilano Pramudya (2022)
IUD contraceptive users during the pandemic have decreased. Based on a survey conducted by the BKKBN, there was a decrease in the percentage of IUD (intra uterine device) use of contraception by 14.24% before the pandemic, to 13.77% after the pandemic, bringing a total decrease of 0.47%. Based on North Jakarta City BPS data, there was a 1.2% decrease in the use of contraception IUDs in Cilincing District in 2019-2021. The purpose of this study was to determine the factors related to the use of IUD contraception in WUS during a pandemic at the Cilincing District Health Center which was carried out during September-December 2021. This study used a cross sectional study design, data collection techniques were simple random sampling with sample size is 150 respondents. The research instrument was a questionnaire in the google form. Data analysis used chi square test (α=0.05). The results showed that factors related to the use of IUD contraception, including education (p value=0.006), knowledge (p value=0.007), husband's support (p value=0.008), access to health facilities (p value=0.007), and socialization. health (p value=0.011). This study concludes that the use of IUD contraception in WUS during a pandemic is influenced by factors of education, knowledge, husband's support, access to health facilities and health socialization. It is hoped that there will be an increase in socialization about IUD contraception to WUS and husbands in increasing knowledge and understanding of the use of IUD contraception.